2020
DOI: 10.4102/sajo.v4i0.91
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the effects of radiotherapy treatment delays on tumour responses: A review

Abstract: Background:The effects of radiotherapy treatment delays vary considerably depending on several factors, including tumour type, tumour characteristics, extent of delay and the radiation schedule. Both delays during treatment and delays in starting treatment may have an impact on tumour outcomes. In developing countries, particularly, budget constraints and overwhelming patient numbers may contribute to long waiting lists that may affect treatment efficacy. Empirical evidence on which to base treatment decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Treatment interruptions beyond 2-7 days reduce the efficacy of radiation treatments. 20 , 21 The uptake of conformal techniques suggests improvement in radiotherapy delivery. However, low utilization rates, underfunding, and poor maintenance contracts prevail.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment interruptions beyond 2-7 days reduce the efficacy of radiation treatments. 20 , 21 The uptake of conformal techniques suggests improvement in radiotherapy delivery. However, low utilization rates, underfunding, and poor maintenance contracts prevail.…”
Section: Discussionmentioning
confidence: 99%
“…treatment gaps) in radiotherapy delivery can significantly compromise treatment success, local tumour control and overall survival. 91,[93][94][95][96] According to Nagar and Formenti, 91 delaying the start of adjuvant radiotherapy over 8 weeks after surgery will double the risk of local recurrence in breast cancer patients and every week of radiotherapy delay beyond 2 weeks after surgery for high-grade gliomas patients increases the risk of death by 8•9%. Several studies have reported a significant impact of the COVID-19 pandemic on radiotherapy delivery in several cancer centres.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Optimal tumor control requires strict adherence to daily treatment scheduling. Unplanned interruptions are associated with inferior outcomes, including reduced overall survival [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Unplanned interruptions are associated with inferior outcomes, including reduced overall survival. 2 , 3 , 4 , 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%